2016
DOI: 10.1016/j.ajic.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Timeline of health care–associated infections and pathogens after burn injuries

Abstract: Background Infections are an important cause of morbidity and mortality after burn injuries. Here, we describe the timeline of infections and pathogens after burns. Methods A retrospective study was performed in a large tertiary care burn center from 2004 through 2013. Analyses were performed on healthcare-associated infections (HAI) meeting Centers for Disease Control and Prevention criteria and on all positive cultures. Incidence rates (IR) per 1,000 days were calculated for specific HAI categories and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
58
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 32 publications
6
58
0
6
Order By: Relevance
“…In contrast, after 1 week of hospitalization, drug-resistant Gram-negative species predominate; e.g., the colonization rates for carbapenem-resistant Enterobacteriaceae increased from 0.004 in week 1 to 0.82 in week 4. Likewise, P. aeruginosa increased from 0.04 to 1.85 , while isolation rates of both P. aeruginosa and K. pneumoniae increased from 1.27 to 2.26 ( P <0.001 for all) [4]. In our study, Gram-negative bacteria were detected in the fourth week, with the presence of P. aeruginosa and K. pneumoniae in the blood stream.…”
Section: Discussionsupporting
confidence: 47%
“…In contrast, after 1 week of hospitalization, drug-resistant Gram-negative species predominate; e.g., the colonization rates for carbapenem-resistant Enterobacteriaceae increased from 0.004 in week 1 to 0.82 in week 4. Likewise, P. aeruginosa increased from 0.04 to 1.85 , while isolation rates of both P. aeruginosa and K. pneumoniae increased from 1.27 to 2.26 ( P <0.001 for all) [4]. In our study, Gram-negative bacteria were detected in the fourth week, with the presence of P. aeruginosa and K. pneumoniae in the blood stream.…”
Section: Discussionsupporting
confidence: 47%
“…2023 Patients tend to start off being colonized with more susceptible Gram-positive organisms early in their hospitalization, whereas after some time in the burn unit, multidrug resistant (MDR) gram-negative bacteria including Pseudomonas aeruginosa tend to predominate. 20 In our hospital, almost half of the pathogens colonizing burn patients were MDR organisms, and the rates of MDR infections increased the longer a patient was hospitalized. Furthermore, the rate of catheter-associated bloodstream infection (CLABSI) has decreased over the past decade, likely due to a bundled intervention introduced to the unit.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described the timeline of HAIs and pathogens among patients with burn injuries, as well as temporal trends in HAIs in our burn unit 20 23 Patients tend to start off being colonized with more susceptible Gram-positive organisms early in their hospitalization, whereas after some time in the burn unit, multidrug resistant (MDR) gram-negative bacteria including Pseudomonas aeruginosa tend to predominate 20 . In our hospital, almost half of the pathogens colonizing burn patients were MDR organisms, and the rates of MDR infections increased the longer a patient was hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is higher than that of the study of Van Duin and his colleagues who identified a rate of 1.78/1000 patient days. 13 However, another comprehensive study of the epidemiology of burn infection showed that the rate among patients with TBSA >30% exceeds 5/1000 patient days. 14 It is worth to mention that our setting is the only referral center for burn patients in the state of Kuwait, so any age group or degree of burn, type of burn injury or TBSA will be receiving management in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…15,20 Van Duin and his colleagues reported that half of the patients who spend 80 days from admission will experience at least one HAI. 13 Also Coetzee et al reported that the risk of wound infection increases by time. 21 Burn wounds are known to be good media for bacterial growth, and colonization occurs shortly after the injury as virulent microorganism strains invade the skin and soft tissue; as the host defense is weak, an increase in the number of microorganisms will be able to reach the venous system to cause infection.…”
Section: Discussionmentioning
confidence: 99%